Describing Passiflora coloranigra, a striking new species of Passiflora supersection Laurifoliae (Passifloraceae) from Panama - Kuethe, J.r.; Meerman, Jan (Phytotaxa, 2022)
After having been incorrectly identified as Passiflora ambigua for years, a new species was revealed during a revision project to the Passiflora supersection Laurifoliae. The morphology of the plant, as well as the coronal structure and colour of the large showy flowers suggest a closer taxonomic relationship with Passiflora nitida rather than Passiflora ambigua. However, the very unusual colour of the corolla and fruit, as well as the location and shape of the petiolar nectaries, are distinctively different from either two species, and the uniquely coloured flowers are among some of the darkest colours seen in Laurifoliae overall. This led to further fieldwork and the eventual conclusion of Passiflora coloranigra sp. nov. Its ecology, taxonomy and association with the other species within Passiflora supersect. Laurifoliae are discussed in this paper.